Enhanced photovoltaic performance for quinoxaline‐based polymeric donor via backbone engineering for non‐fullerene organic solar cells. (16th September 2022) - Agneeswari, Rajalingam; Ahn, Yoomi; Tamilavan, Vellaiappillai; Kim, Danbi; Shin, Insoo; Yi, Hojun; Shin, Chnan‐gi; Park, Sung Heum; Jin, Youngeup
Abstract: Herein, we demonstrate a facile technique for transforming a low‐energy‐converting quinoxaline‐based polymer into an efficient polymeric donor for non‐fullerene acceptor‐based organic solar cells (NFA‐OSCs). Alternating copolymers, namely P(BDTSi‐DTfQ), incorporating electron‐rich 4, 8‐bis(triisopropylsilylethynyl)‐benzo[1, 2‐b:4, 5‐′]dithiophene (BDTSi) and electron‐deficient 2, 3‐didodecyl‐6‐fluoro‐5, 8‐di(thiophen‐2‐yl)quinoxaline (DTfQ) units were synthesized. The properties of P(BDTSi‐DTfQ) were thoroughly studied and briefly compared to those of the reported polymers, namely P(BDTSi‐DTffQ), made up of BDTSi and 2, 3‐didodecyl‐6, 7‐difluoro‐5, 8‐di(thiophen‐2‐yl)quinoxaline (DTffQ) units. Polymer P(BDTSi‐DTfQ) exhibited a lower bandgap ( E g ) and higher highest occupied and lowest unoccupied energy levels (HOMO and LUMO) than P(BDTSi‐DTffQ). The estimated Eg and HOMO/LUMO for P(BDTSi‐DTfQ) were 1.90 eV and −5.46 eV/−3.56 eV, respectively, and for P(BDTSi‐DTffQ) the same were 1.94 eV and −5.58 eV/−3.64 eV, respectively. Interestingly, the NFA‐OSCs made from P(BDTSi‐DTfQ) as the donor and NFA, namely ITIC, as the acceptor, gave a power conversion efficiency (PCE) of 3.68%, which is much higher than the PCE obtained (⁓0.75%) for the OSCs prepared by using the P(BDTSi‐DTffQ):ITIC blend. Noticeably, the energy levels of P(BDTSi‐DTfQ) were found to be favorable for efficient charge separation when it was blended with ITIC. This blend not only allowed a better charge separation at the donor/acceptor interfaces but also significantly lowered bimolecular recombination. The overall effect was to provide a higher PCE. However, P(BDTSi‐DTffQ) showed mismatched energy levels with ITIC resulting in a higher bimolecular recombination and lower PCE. Abstract : Fluorine atom influences on the photovoltaic properties of polymeric donors were studied by comparing the properties of structurally similar polymers, P(BDTSi‐DTfQ) and P(BDTSi‐DTffQ), incorporating mono and difluoro substituents on their backbones. Overall, the dissimilar photovoltaic performances for P(BDTSi‐DTfQ) and P(BDTSi‐DTffQ) were found to be attributed to their energy levels and that were influenced by the fluorine substituents.